Find the sum of the following
(– 6/13) + (– 14/26)
Answers
Answered by
2
Bonjour!
![= > ( - \frac{6}{13} ) + ( - \frac{14 }{26} ) \\ \\ = > - \frac{6}{13} - \frac{14}{26} \\ \\ = > \frac{ - 12 - 14}{26} \\ \\ = > - \frac{26}{26} \\ \\ = > - 1 = > ( - \frac{6}{13} ) + ( - \frac{14 }{26} ) \\ \\ = > - \frac{6}{13} - \frac{14}{26} \\ \\ = > \frac{ - 12 - 14}{26} \\ \\ = > - \frac{26}{26} \\ \\ = > - 1](https://tex.z-dn.net/?f=+%3D++%26gt%3B+%28+-++%5Cfrac%7B6%7D%7B13%7D+%29+%2B+%28+-++%5Cfrac%7B14+%7D%7B26%7D+%29+%5C%5C++%5C%5C++%3D++%26gt%3B++-++%5Cfrac%7B6%7D%7B13%7D++-++%5Cfrac%7B14%7D%7B26%7D++%5C%5C++%5C%5C++%3D++%26gt%3B++++%5Cfrac%7B+-+12+-+14%7D%7B26%7D++%5C%5C++%5C%5C++%3D++%26gt%3B++-++%5Cfrac%7B26%7D%7B26%7D++%5C%5C++%5C%5C++%3D++%26gt%3B++-+1)
Hope this helps...:)
Hope this helps...:)
Answered by
3
(-6/13)+(-14/26) = (-12/26)+(-14/26)
= (-12-14)/26 = -26/26 = -1
thus (-6/13)+(-14/26) = -1
= (-12-14)/26 = -26/26 = -1
thus (-6/13)+(-14/26) = -1
Similar questions